(untitled) (Nexo Revista Científica, 2021)
Dam projects have serious influences on environmental parameters; therefore, environment risk assessment of dam is one of the most significant aspects of environmental risk management in these projects. The present study was conducted with the aim of presenting a new model for assessing the environmental risk of dams in construction stage. After identifying environmental risks and using the EFMEA method, the risk priority number for each of the environmental aspects was calculated and classified. Then, to assess and prioritize the identified environmental risks, the VIKOR method was used. The results showed that in The EFMEA method and by comparing calculated risk numbers, the risk of water pollution of Balarood River with the risk priority number of 125 is in the first priority. In the VIKOR method, the risks of water pollution in terms of agreement (high, average, low) with weights (1,300, 1,000 and 0,700) were identified as the most important risks. In the present article, using EFMEA and VIKOR methods in the environmental risk assessment of the dam, the most important risks were determined. The most important proposed corrective measure to reduce the environmental risks is the construction and completion of wastewater treatment for industrial units.